Cost-effectiveness analysis of selexipag for the combined treatment of pulmonary arterial hypertension - Dong, Wenxing; Zhang, Zhe; Chu, Mingming; Gu, Peng; Hu, Min; Liu, Lulu; Huang, Jingbin; Zhang, Rong (Frontiers in Pharmacology, 2023)
Objective: Adding selexipag to the combined treatment of endothelin receptor antagonists (ERA) and phosphodiesterase 5 inhibitor (PDE5i) reduces the risk of clinical worsening events in patients with pulmonary arterial hypertension (PAH) but at a considerably higher cost. This study evaluated the costeffectiveness of adding selexipag to the combined treatment of ERA and PDE5i in patients with PAH from a Chinese healthcare system perspective.Methods: A Markov model was developed to assess costs and quality-adjusted life years (QALYs) of macitentan + tadalafil + selexipag vs. macitentan + tadalafil for the treatment of PAH. Markov states included WHO Functional Class (FC) (I-IV) and death. Transition probabilities were based on data from the TRITON trial. Mortality rates, costs, and utilities were obtained from published literature and public databases.In the base case analysis, compared with macitentan + tadalafil, selexipag + macitentan + tadalafil increased costs (357,807.588 vs. 116,534.543, respectively) and QALYs (7.234 QALYs vs. 6.666 QALYs, respectively). The resulting incremental cost-effectiveness ratio was 424,746.070 per QALY, which was higher than the willingness-to-pay (WTP) of 38,223.339 per QALY. The results2 were most sensitive to HR for mortality of patients with FC IV relative to the general population, discount rate, and the cost of selexipag. The probability was greater than 50% for the selexipag + macitentan + tadalafil only if the WTP was more significant than 426,019.200 per QALY.In China, adding selexipag may not be cost-effective for patients with PAH who failed to control their condition after combined treatment of ERA and PDE5i. Results of the analysis can aid discussions on the value and position of selexipag for the combined treatment of PAH.